Gambaran Sikap Remaja Putri dalam Mencegah Pernikahan Usia Dini di SMA X Kecamatan Tanjungsari, Kabupaten Sumedang, Jawa Barat - Debby Janette; Mamat Lukman; Dadang Purnama (Lembaga Pengembangan Kinerja Dosen, 2025)
Early marriage remains a serious issue that affects education, reproductive health, and increases the risk of stunting in children. Adolescents, as a vulnerable age group, are in a formative stage of attitude development, making it essential to understand their tendencies in facing this issue. This study aims to describe the attitudes of female adolescents in preventing early marriage at SMA X, Tanjungsari District, Sumedang Regency, West Java . The research employed a descriptive quantitative design with a cross-sectional approach and involved 144 respondents selected through proportional stratified random sampling. Data were collected using the Early Marriage Attitude Scale (EMAS) and analyzed using frequency distribution and percentages. The results showed that 77 respondents (53.5%) had a positive attitude toward preventing early marriage, while 67 respondents (46.5%) showed a negative attitude. The spiritual belief dimension recorded the highest percentage of positive attitudes (72.9%), followed by the parent-child relationship dimension (66%) and parental economic hardship (66%). The social norms dimension appeared the most balanced, indicating that cultural and social pressures continue to significantly influence adolescent attitudes. Age and family income were also influential; respondents aged 17 and from middle-to-upper-income families tended to exhibit more positive attitudes. These findings imply the need to strengthen reproductive health education, family-based approaches, and adolescent empowerment programs rooted in spiritual values and self-control to sustainably support the prevention of early marriage.